Determinants of Nurses’ Performance at Regional Hospital - Lulu Ananda Putri; Maryana Maryana; Nova Mardiana (Genius Journal, 2026)
Introduction: Nurse performance plays a vital role in determining the quality of healthcare services and hospital outcomes. Various factors, including education level, work motivation, and the work environment, have been identified as key determinants influencing nurses’ ability to deliver optimal nursing care. However, disparities in nurse performance and increasing service demands highlight the need for empirical analysis of these factors within hospital settings. Objective: Nurses are professionals who possess intellectual, technical, interpersonal, and moral abilities, are responsible for, and have the authority to provide nursing care in health services. The purpose of this study was to determine the relationship between education, work motivation, and work environment on nurse performance at RSUD Junjung Besaoh, Bangka Selatan Regency, in 2025. Method: This study used a cross-sectional design with independent variables (education, work motivation, and work environment) and dependent variables (nurse performance). The sample size was 61, and the study period was July 7–13, 2025. Result: The results of the study using the Chi-Square Test were as follows: education p-value 0.000 <0.05, work motivation p-value 0.003 <0.05, and work environment p-value 0.000 <0.05. This indicates a significant relationship between education, work motivation, and the work environment on nurse performance at RSUD Junjung Besaoh, Bangka Selatan Regency in 2025. Conclusion: This study are expected to benefit researchers in broadening their knowledge and insights, and serve as reference material for further research and development in the application of nursing care.